2012
DOI: 10.3892/ijo.2012.1453
|View full text |Cite
|
Sign up to set email alerts
|

CD44 enhances the epithelial-mesenchymal transition in association with colon cancer invasion

Abstract: Abstract. The metastatic process involves the migration and invasion of cancer cells throughout the body to produce secondary tumors at distant sites. Through of epithelial-mesenchymal transition (EMT), cancer cells employ developmental processes to gain migratory and invasive properties. CD44 is the transmembrane adhesion receptor for Hyaluronan (HA) and plays a central role in the remodeling and degradation of HA that leads to cell migration, as well as to cancer invasion and metastasis. CD44 is highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…HMGA2 elicits EMT by activating a series of transcription factors 24,25 , while CD44 participates in the downregulation of E-cad commonly observed during EMT 12,28 . Immunohistochemically, there were no specific cross-reactivity of the HMGA2 selected antibody with feline tissue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HMGA2 elicits EMT by activating a series of transcription factors 24,25 , while CD44 participates in the downregulation of E-cad commonly observed during EMT 12,28 . Immunohistochemically, there were no specific cross-reactivity of the HMGA2 selected antibody with feline tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, EMT-derived cells are usually characterized by a higher HMGA2 expression 9,26 , loss or reduced expression of E-cadherin (E-cad), up-regulation of vimentin (Vim) 7,9 , and co-expression of epithelial markers (cytokeratins [CKs]) and mesenchymal markers (calponin [CALP], smooth muscle actin [SMA], and Vim) 7,27 . Other markers like CD44 participate in the downregulation of E-cad 12,28 . Consequently, EMT-derived cells are characterized by a higher CD44 expression 8,28 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that HMW-HA enhances EC barrier function (Singleton et al, 2006, 2010). The HA in the stroma of several cancers has been implicated in numerous processes including inhibition of apoptosis, stimulation of tumor cell proliferation, migration and invasion, epithelial mesenchymal transition, protection from immune cells, and regulation of intercellular space (Auvinen et al, 2013; Bollyky et al, 2009; Cho et al, 2012; Dickinson & Gerecht, 2010; Sironen et al, 2011; Tammi et al, 2008). Whether this stroma-associated HA also promotes resealing of new capillaries remains to be determined.…”
Section: Ha Regulation Of Endothelial Barrier Function During Tumomentioning
confidence: 99%